Palliative Approach in Advanced Pelvic Osteosarcoma: a Single Centre Experience of a Rare Disease - Kumar, Ritesh (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Pelvic osteosarcoma is a rare and aggressive malignant neoplasm with poor outcomes. It represents only 5% of all osteosarcomas. The authors present our institute's experience in management and outcomes of five successive patients of pelvic osteosarcoma. MATERIALS AND METHODS: We retrospectively reviewed five patients of pelvis osteosarcoma treated in our institute from September 2008 to December 2010. Clinical characteristics and treatment (CCT) modality in form of surgery and chemotherapy were noted. Statistical analysis was done with regards to progression-free survival (PFS) using Kaplan-Meier survival analysis. RESULTS: The median age of the patients was 16.0 years. The median duration of symptoms was 9 months. One patient had lung metastases at presentation. All patients received systemic chemotherapy. One patient underwent surgery in the form of limb sparing approach. Three patients had partial response to treatment, one had complete response, and one had progressive disease. Median duration of PFS was 7 months only. CONCLUSIONS: Pelvic osteosarcomas are rare neoplasms with aggressive growth patterns. Survival results are poor in view of advanced stage of presentation and difficult surgical approaches. The combined modality approach is needed to improve the results.